GAMBARAN KADAR C REACTIVE PROTEIN (CRP) TERHADAP PASIEN YANG MENGALAMI INFEKSI SALURAN PERNAPASAN - suardi; Dewi Arisanti; A. Macmun Raihan Mursidiq (Klinikal Sains : Jurnal Analis Kesehatan, 2025)
Respiratory tract infections (RTIs) are one of the most common diseases and have the potential to cause systemic inflammatory responses. The inflammatory process triggers the liver to produce C-Reactive Protein (CRP). Therefore, CRP testing can be used as an indicator of inflammation and to support clinical diagnosis. The latex agglutination method is a simple and rapid technique for detecting CRP qualitatively and semi-quantitatively. The type of study used was an observational laboratory study employing accidental sampling with a sample size of 20 serum samples from patients exhibiting clinical symptoms of RTI. This study aimed to determine the results of CRP testing using the latex agglutination method in patients with suspected respiratory tract infections. The test results showed that of the 20 serum samples, 12 samples (60%) were CRP positive and 8 samples (40%) were negative. It was concluded that the majority of patients with suspected respiratory tract infections showed positive CRP results, indicating the presence of active systemic inflammation. Keywords: Semi-Quantitative Agglutination, C-Reactive Protein, Respiratory Tract Infection, Inflammation